Effect of Rhizobia Inoculation on Nodulation and Yield of Moong [Vigna Radiata (L) Wilczek] - Singh, S (Annals of Arid Zone, 2016)
Effects of rhizobium inoculation on nodulation and yield of moong crop variety 'RS4' were studied. A small amount of nitrogen and phosphorus promoted nodulation on inoculated plants. However, inoculated unfertilized plant nodulated profusely during the normal period of branching and flower primordial initiation .. This may be the possible reason for the highest number of riped pods on inoculated control plant. Through a such gain in important yield contributing character, inoculated control crop gave 51 per cent higher yield than uninoculated control. For a nominal inoculation cost of Rs 8/ha, such yield gains are bound to grip the attention of farmers. Yield gain of this magnitude could not be obtained either from 20 kg/ha of nitrogen, or 30 kg/ha of phosphorus, or the two applied together. As far these data show, rhizobia inoculation alone obviates the need for fertilizer nitrogen and phosphorus in rnoong crop to be grown under natural rainfall conditions.